A experiência de doença em mulheres com câncer de mama no contexto de um grupo de apoio - Almeida, Daiane Riva de (Universidade do Vale do Rio dos Sinos, 2013)
The study investigated the experience of illness in women with breast cancer within a support group. The study included ten women aged between 39 and 81 years, who attended the Oncology Support Group Holding Hands of Novo Hamburgo / RS. This was a qualitative study involving participant observation and semi-structured interviews with the group for mutual support between March and July 2013. The accounts of participants and field notes were examined through thematic content analysis. The results showed that group membership potentialized the cozy environment, the sharing of experience, information and active coping individual and collective of the illness, expanding the network of relationships and support between the women. Amid the emotional shock of the diagnosis and treatment challenges, the space provided to the group also assisted in the rescue of self-esteem and sense of control over their lives, empowering them and providing opportunities for standardization mechanisms, when the focus of life could deviate from the illness. The findings also highlighted the difficulties faced by the collective of women as their liaison with managers and with networks of health care that often gave no echo to their demands and to their role for a more comprehensive and humane care to women with breast cancer. It is understood that the effective action and everyday policies and health services in legitimizing intersectoral and participatory management that promote community partnerships and support networks of popular initiative in the area of women's health is still a challenge.
Keywords: Câncer de mama; Neoplasia mamária; Apoio social; Grupo de autoajuda; Breast cancer; Breast neoplasy; Social support; Self-help group; ACCNPQ::Ciências da Saúde::Saúde Coletiva